Abacavir has no prothrombotic effect on platelets in vitro. (11th August 2016) - Diallo, Yacouba L.; Ollivier, Véronique; Joly, Véronique; Faille, Dorothée; Catalano, Giovanna; Jandrot-Perrus, Martine; Rauch, Antoine; Yeni, Patrick; Ajzenberg, Nadine
Abstract : Objectives: HIV patients exposed to abacavir have an increased risk of myocardial infarction, with contradictory results in the literature. The aim of our study was to determine whether abacavir has a direct effect on platelet activation and aggregation using platelets from healthy donors and from HIV-infected patients under therapy with an undetectable viral load. Methods: Platelet-rich plasma (PRP) or whole blood from healthy donors was treated with abacavir (5 or 10 μg/mL) or its active metabolite carbovir diphosphate. Experiments were also performed using blood of HIV-infected patients ( n  = 10) with an undetectable viral load. Platelet aggregation was performed on PRP by turbidimetry and under high shear conditions at 4000 s −1 . Platelet procoagulant potential was analysed by measuring thrombin generation by thrombinography. Results: Abacavir and carbovir diphosphate significantly increased the aggregation of platelets from healthy donors induced by collagen at 2 μg/mL ( P  = 0.002), but not at 0.5 μg/mL. No effect of abacavir or carbovir diphosphate was observed on platelet aggregation induced by other physiological agonists or by high shear stress, or on thrombin generation. Pretreatment of blood from HIV-infected patients with abacavir produced similar results. Conclusions: Our results suggest that abacavir does not significantly influence platelet activation in vitro when incubated with platelets from healthy donors or from HIV-infected patients. It is, however, not excluded that a synergistic effect with other drugs could promote platelet activation and thereby play a role in the pathogenesis of myocardial infarction.